Eficiência e equidade: impactos econômicos de uma reforma tributária com Imposto sobre Valor Adicionado (IVA) - Ana Tereza Pereira Libânio (2021)
In view of the current debate on the importance of restructuring the tax system of a country, this dissertation studies the impacts of a reform in consumption taxation in Brazil that unifies taxes in a VAT type tax. The impacts of replacing the IPI, PIS, Cofins, ICMS and ISS on economic activity, sectors, representative families, 11 income classes and income distribution were projected. To do so, BRIGHT (Brazilian Social Accounting - General Equilibrium Model for Income Generation, Households and Transfers) was used, a computable general equilibrium model with elements of recursive dynamics that incorporates the circular flow of income through an accounting matrix (MCS). This model has a breakdown of 11 family groups and direct and indirect taxes. Up to 2030, three different scenarios were projected with the following VAT rates: 20, 25 and 30%. The results show that the change in the tax structure would present growth gains for the GDP and its components but with a modest increase in household consumption. Sectors such as services would be the most burdened by the reform, while the industry would benefit. The effect on family income is heterogeneous according to the family's class. The families of the lower and middle classes would obtain an increase in disposable income, while the households of higher classes would present a decrease in the indicator. In conclusion, a change in indirect taxation in Brazil with the implementation of a VAT would generate not only efficiency gains but also distributive ones, presenting a decline in the Gini index for the three analyzed scenarios.